Association of serum carotenoids and SII among general people, based on NHANES 2001–2006 - Shao-Hua Yan; Wenqing Nai; LuShan Peng; Junpu Wang (Scientific Reports)
Abstract As a novel inflammatory marker, Systemic Immune-Inflammation Index (SII) has recently been recognized as a prognostic indicator for a variety of diseases including malignant cancers, coronary artery disease, hyperlipidemia, and hepatic steatosis. Carotenoids are a group of abundant lipid-soluble phytochemicals, and studies have suggested that they have antioxidant, antiapoptotic, and anti-inflammatory properties. However, a systematic analysis of the association between serum carotenoids and SII is still lacking. The purpose of this investigation was to explore the association between serum carotenoid concentration and SII. The cross-sectional investigation included general people (age ≥ 20) with complete information on SII and five different serum carotenoids (Trans-lycopene, β-carotene, α-carotene, lutein/zeaxanthin, and β-cryptoxanthin). Multivariate linear regression analyses were used to evaluate the association between serum carotenoids and SII among general people. The potential non-linear relationship was determined using threshold effect analysis and fitted smoothing curves. Subgroup analysis was performed to explore the potential stratified factors. 15903 participants were enrolled in our investigation. Based on multivariate linear regressions, the highest quartiles of serum carotenoids were found significantly associated with SII compared with the lowest quartiles. The results showed the negative association between SII and the concentration of five different serum carotenoids. According to the non-linear analysis, we found that there are non-linear relationships between β-carotene and trans-lycopene and SII in general people with an inflection point of 6.90 (log2-transformed, ug/dL) and 4.01 (log2-transformed, ug/dL), respectively. The results from subgroup analysis provide several potential moderating effects, such as race, current drinker, and age. This study revealed the relationship between the concentration of several serum carotenoids and SII across the general American population. Further prospective and longitude investigations are needed.